OPERATIONAL RISK MANAGEMENT IN GLOBAL SUPPLY CHAINS: THE ROLE OF BLOCKCHAIN IN ENHANCING TRACEABILITY - Pratiwi, Nurul Aziz (Penelitian dan Pengembangan Ilmu, 2025)
Operational Risk Management (ORM) is crucial for maintaining global supply chain resilience, but disruptions can increase costs, reduce quality, and cause significant financial losses, as evidenced by a 26% increase in cargo theft incidents by 2024, with estimated losses exceeding USD 1 billion. Enhanced traceability is key to risk mitigation, in line with the projected blockchain traceability market reaching USD 44.3 billion by 2034. This study examines how blockchain adoption impacts ORM through improved traceability using a narrative synthesis of peer-reviewed articles from 2015–2025 in Scopus, Web of Science, ScienceDirect, and Google Scholar. The analysis focuses on blockchain-based traceability mechanisms, the types of risks addressed, and the impact on risk mitigation. The results show that blockchain enhances traceability through immutable, transparent, and decentralized data records, reducing fraud, counterfeiting, and compliance issues. Smart contracts enable process automation, reducing delivery delays, and increasing efficiency. These findings are supported by the Transaction Cost Economics (TCE), Resource-Based View (RBV), and Supply Chain Risk Management (SCRM) frameworks, emphasizing transaction cost reduction, competitive advantage, and risk mitigation. Blockchain plays a strategic role in transforming global supply chains, although implementation faces challenges related to cost and integration of legacy systems. Further studies are recommended using quantitative and longitudinal approaches for long-term evaluation.